Pengaruh Lokasi dan Store Atmosphere Terhadap Minat Beli Ulang Kafe Bagus di Motoboi Kecil - Evi Aurellia Babay; Siti Nurjanah (UNIVERSITAS KALBIS, 2022)
This research was conducted with the aim of knowing the effect of the location and the Store Atmosphere of Kafe Bagus on Consumer Repurchase Intention. This study uses a quantitative method with incidental sampling technique but with certain criteria. The sample used was 246 respondents with the criteria of being Kafe Bagus consumers who directly felt the food and atmosphere of Kafe Bagus. As well as data processing using the SPSS program. The results of the hypothesis testing show that the location and store atmosphere partially each have a positive and significant effect on repurchase intention of Kafe Bagus consumers. As well as simultaneously, the location and store atmosphere have a significant effect on repurchase intention of Kafe Bagus consumers.